Variable Pay, Industrial Relations and Foreign Ownership: Evidence from Germany - John S. Heywood; Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2011)
We estimate of the determinants of performance appraisal, profit sharing and employee share ownership schemes for a representative sample of German establishments. The results demonstrate that foreign owned establishments make more use of each of these HRM practices than domestically owned establishments. Moreover, the role of Germany's unique works councils varies critically by ownership. Among domestically owned establishments, works councils are associated with an increased probability of using each of the three practices but this does not hold true for foreign owned establishments. These results inform the on-going debate over the extent to which foreign firms adopt uniform practices independent of local institution and the extent to which they adapt and participate in those local institutions.
Keywords: F23; J33; J53; M52; 330; Foreign Owners; Works Councils; Performance Appraisal; Profit Sharing; Employee Share Ownership